Cause we are living in a Machiavellian world, and I am a Machiavellian major: Machiavellianism and academic major choice - Gruda, Dritjon (2023)
Students from diverse academic majors differ in their personalities. However, the study of the association between Machiavellianism (i.e., desire for power, status, and social dominance) and educational choices (i.e., academic major choices) that lay a path toward occupations that allow for those outcomes has been largely ignored. Using a large multinational sample of 35,025 participants across 50 majors, we found overall support for a significant association between Machiavellianism and academic major choice. We break down the results by sex and provide a cross-country comparison.